"I Don't Want My Children to Work so Hard": Perceptions of Parent-Child Relationships and Future Parenting Among Immigrant Young Adults. (June 2022) - Yakhnich, Liat; Michael, Rinat
Immigration is a multifaceted process that alters parent-child relationships and impacts immigrant children's development. However, not much is known regarding the long-term implications of immigration on children when they reach adulthood. This phenomenological study explored the perceptions of parent-child relationships among young adults who immigrated as children to Israel, and the ways such relationships shaped their future parenting perceptions. Twenty-five young adults who immigrated to Israel in middle and late childhood from Ethiopia ( n  = 14) and from the former Soviet Union ( n  = 11) were interviewed for this study. Analysis indicated that the participants' experiences of relations with their parents may be organized into three main domains: shifting relations in the context of immigration, relations in the context of long-term adaptation and maturation, and relations in cultural context (e.g., cultural perceptions about family life and culture-related immigration challenges). Participants' perceptions of their own parenting incorporated culture-specific factors (e.g., family hierarchy and cohesiveness, child-rearing practices, and respect given to parents) as well as difficulties and strengths experienced by the participants' families during immigration. Although most participants wished to be different from their parents (not wanting their children to work so hard) they hoped to preserve some of their culture of origin's child-rearing practices. The findings have implications for professionals who work with immigrant families and for policy makers. Considering a family's specific cultural background and helping parents integrate diverse parental practices may assist immigrant families in coping with challenges of immigration and help young adults who immigrated as children in creating a coherent parenthood.